Investigation of Epoxy/Waste Banana Skin Fruit with Organic Filler Composite upon Biodegradation. - Chia, Kie Tick (2015)
In this study, the aim is to investigate the characterization properties of polymer thin film epoxy/ waste banana skin fruit with eggshell as filler for composite and the biodegradation of polymer thin film epoxy/banana skin fruit with eggshell composite upon natural soil burial test. Bio-composite polymer thin film is produced by using the waste banana skin fruit as the reinforcement fiber, eggshell as filler and epoxy resin as matrix. The thickness of the thin film was in between 0.10mm to 0.15mm. Epoxy/Waste Banana Skin Fruit with Eggshell (EWE) 0%, EWE 5%, EWE 10% and EWE 15% are prepared by adding different percentages of organic filler (eggshell) into the composite. These bio-composite polymer thin films were plant at two different types of soil, compost soil and land use soil for 70 days. The weight loss, visual observation and the analysis by optical microscope of the bio-composite polymer thin film in each type of soil was determined. Besides, the soil pH value was determined. In this study, the percentage of weight loss of polymer composite upon compost soil is higher than the polymer composite upon land use soil. This is due to the present of many microorganisms in the compost soil. Furthermore, the higher of the percentage of eggshell in the polymer composite, the lower of the percentage of weight loss occur. The pH value of compost soil and land use soil are slowly increased when the time increase, this is due to the waste of eggshell has high content of calcium and nitrogen that can be used as fertilizer. In visual observation, its shows that there were huge morphological changes on the polymer composite after a various times intervals. In analysis by optical microscope, visible erosion was detected on the surface due to the biodegradation of polymer composite, which caused permanent damage to the material.